Treatment of a horizontal root-fractured tooth with decoronation procedure: case report - Selen Esin Yoldaş; Haluk Cengiz Bodur; Sercan Küçükkurt (Gazi University, 2016)
INTRODUCTION: Early loss of permanent anterior teeth due to trauma can cause esthetic and functional problems for young patients. In such cases, replacement of the missing tooth with traditional approaches is possible; however such approaches will reduce the chance of the patient to receive an esthetic and consistent treatment in the future. CASE REPORT: A 12-year-old male patient referred to our clinic with a history of trauma. Complicated crown fracture in tooth no.11 and horizontal root fracture in tooth no. 21 was detected. Following root canal treatment, tooth no. 11 was restored with a fiber post and a strip crown. To avoid alveolar bone loss due to early tooth extraction, decoronation procedure, an alternative approach, was applied to tooth no. 21. This procedure consisted of leaving the root fragment inside the alveolar socket following the removal of the crown. For the rehabilitation of the missing crown, a partial removable prosthesis was implemented. The patient was recalled in 6., 12. and 18. months. Within the follow-up period, no reduction in the alveolar bone level was seen. No sign of infection was evident. The remaining root fragment kept on resorbing. Tooth no. 11 remained symptom-free as well. The patient is still being followed. CONCLUSION: Decoronation is essentially a treatment choice for preventing alveolar bone loss in ankylosed teeth considered for extraction. In this case report, decoronation was shown to be a suitable alternative also for a fractured, non-ankylosed tooth.